1998
DOI: 10.1212/wnl.51.5.1447
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotype of the 8344 transfer RNA lysine mitochondrial DNA mutation

Abstract: The A-to-G mutation at position 8344 in the transfer RNAlysine mitochondrial DNA gene is associated mostly with the myoclonic epilepsy and ragged red fibers syndrome. We describe a five-generation family with this mutation and 19 affected members with a variant neurologic syndrome of ataxia, myopathy, hearing loss, and neuropathy. Along with axial lipomas and diabetes mellitus, hypertension is a frequent somatic feature, suggesting that mitochondrial mutations may contribute to hypertension in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 2 publications
3
33
0
Order By: Relevance
“…These features are neither common nor specific to mitochondrial diseases, but they may both have been overlooked to date, because they are frequent in the general population and difficult to relate to mitochondrial dysfunction 40, 41, 42, 43. However, the striking similarity of both probands from each family (III:7 in Family 1 and III:1 in Family 2) and further recurrence of these features in other individuals suggest that both hypertension and anxiety disorder may be underestimated features in mitochondrial diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These features are neither common nor specific to mitochondrial diseases, but they may both have been overlooked to date, because they are frequent in the general population and difficult to relate to mitochondrial dysfunction 40, 41, 42, 43. However, the striking similarity of both probands from each family (III:7 in Family 1 and III:1 in Family 2) and further recurrence of these features in other individuals suggest that both hypertension and anxiety disorder may be underestimated features in mitochondrial diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that synapsis of homozygous chromosomes in the mammalian spermatogenic meiotic process begins at the zygotene stage through chromosome movement and attachment [6,24] and that several factors for synaptonemal complexes of homozygous chromosomes, such as RAD51, DMC1, and cohesin, contain functional ATP binding domains [1,30,43]. Actually, abnormal and incomplete attachment of homozygous chromosomes occurred only in mito-mice∆ with a high load of ∆mtDNA.…”
Section: Male Infertility In Mito-mice∆mentioning
confidence: 99%
“…Dementia and ataxia are sometime found in patients with traditional mitochondrial diseases caused by accumulation of mutated mtDNAs, such as MELAS (mitochondrial encephalopathy, lactic acidosis, and strokelike episodes), MERRF (myoclonic epilepsy and ragged red fibers), KSS (Kearns-Sayre Syndrome), CPeO (chronic progressive external ophthalmoplegia), and NARP (neurogenic muscle weakness, ataxia, and retinitis pigmentosa) [1,6,13,24,30,43], and the same mutated mtDNAs have been identified in patients with dementia, ataxia, and Alzheimer's disease [31,42]. Moreover, there appears to be a relationship between mtDNA polymorphisms and cognitive function in humans [38].…”
Section: Abnormalities Of Spatial Remote Memory In Mito-mice∆mentioning
confidence: 99%
“…We could speculate that if this polymorphism really exerts a large effect on BP this should have been reflected by an augmented incidence of CV events, as for other polymorphisms we tested in the same cohort [310,32]. Finally, since Goring and colleagues, using a genome-wide transcriptional profiles of lymphocyte samples, identified the cis-regulated VNN1 as harbouring sequence variants that influence HDL-cholesterol concentrations, in an exploratory analysis we evaluated also a possible Fava et al 12 effect of the T26I SNP on HDL-cholesterol and other components of the metabolic syndrome but without any evidence of association in both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subjects with genetic and acquired forms of mitochondriopathy have an impaired respiratory chain with subsequent production of ROS and a tendency to higher levels of BP [12][13][14].…”
Section: Introductionmentioning
confidence: 99%